2000
DOI: 10.1149/1.1393226
|View full text |Cite
|
Sign up to set email alerts
|

“Lithium-Free” Thin-Film Battery with In Situ Plated Li Anode

Abstract: It is an old concept to fabricate lithium batteries in the discharged state with only an appropriate current collector as the negative electrode (anode). On the initial charge, metallic Li is electroplated at this anode current collector, and so, during electrochemical cycling, the battery operates as a Li battery which contains only the amount of lithium that is supplied by the positive electrode (cathode).Despite some improvements, 1 the manufacture of a practical, rechargeable Li battery that operates exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
345
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(380 citation statements)
references
References 18 publications
5
345
0
1
Order By: Relevance
“…Therefore, lithium-ion or 'lithium-free' cell designs, 11,12 and consequently lithiated materials at the positive electrode, are preferably envisaged for microbatteries with improved performance. In this context, the aim of this study was to develop a new lithiated positive electrode material with possible 3 advantages over the widespread LiCoO 2 cathode material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lithium-ion or 'lithium-free' cell designs, 11,12 and consequently lithiated materials at the positive electrode, are preferably envisaged for microbatteries with improved performance. In this context, the aim of this study was to develop a new lithiated positive electrode material with possible 3 advantages over the widespread LiCoO 2 cathode material.…”
Section: Introductionmentioning
confidence: 99%
“…2a, right panel). Each individual battery with an active area of 2.25 × 1.7 mm micro-cell, deploys a "lithium-free" lithium-ion battery construction 26 in which the anode plays the same role as the current collector, avoiding the dangers associated with reactive lithium metal. Such small size cells are attractive for miniaturized implantable flexible systems.…”
Section: Resultsmentioning
confidence: 99%
“…4 Neudecker et al have reported that Li-free thin-film batteries with the cell configuration Cu/LiPON/LiCoO 2 showed large irreversible capacities during the initial cycle. 5 Okita et al have recently proposed that lithium dissolution and deposition properties were improved by insertion of platinum layer at the Cu/ LiPON interface; lithium-platinum alloy increased reaction sites, resulting in reducing the overvoltage of the lithium dissolution and deposition reaction in thin-film batteries. 6 Bulk-type batteries also have a possibility of operating as rechargeable lithium metal batteries with high capacities.…”
Section: Introductionmentioning
confidence: 99%